Empowering Adolescents in Stunting Prevention: A Literature Review on Educational Media and Methods - Dwisafril Hairil, Ria; Ahmad, Mardiana; Budu, Budu; Handayani Idrus, Hasta (Journal of Neonatal Surgery, 2025)
Introduction: The Indonesian Health Survey (IHS) data in 2023 stated that the prevalence of stunting was 21.5%. One form of handling stunting with nutrition and health education, especially for adolescents who will later give birth to a healthy generation. Methode: The literature review is based on national and international scientific journals on educating adolescents on stunting management. Publications between 2019-2024 databases; PubMed, ScienceDirect, Google Scholar, and Semantic Scholar. Obtained by using keywords; education, teenager, handling, stunting. There were 105 articles identified, then 80 literatures were screened. Further selection related to abstract, full text, open access type of research obtained 50 articles. The final process is to read and select eligible articles based on the criteria obtained 30 relevant articles consisting of 10 international journals and 20 national journals with the Population is all adolescent girls. Result: There were 30 articles that met the criteria, explaining about adolescents, stunting and education for adolescents about handling stunting and the media used in education for handling stunting. Educational media are booklets, audio, whatsapp, social media, stunting prevention cards while educational methods are training and brainstorming. Conclution; Educational outreach can improve adolescents‘ knowledge of nutritional intake (iron and protein), understanding of 1000 HPK and Fe tablet consumption as well as improve adolescents’ attitudes and behaviour in stunting prevention. Education can provide significant results that must be supported by media. The delivery of education using good media such as videos, digital booklets, whatsapp and Stunting Prevent Card will make it easier for adolescents to understand the educational material presented.